Identification of a conserved S2 epitope present on spike proteins from all highly pathogenic coronaviruses - Rui P Silva; Yimin Huang; Annalee W Nguyen; Ching-Lin Hsieh; Oladimeji S Olaluwoye; Tamer S Kaoud; Rebecca E Wilen; Ahlam N Qerqez; Jun-Gyu Park; Ahmed M Khalil; Laura R Azouz; Kevin C Le; et al. (eLife, 2023)
To address the ongoing SARS-CoV-2 pandemic and prepare for future coronavirus outbreaks, understanding the protective potential of epitopes conserved across SARS-CoV-2 variants and coronavirus lineages is essential. We describe a highly conserved, conformational S2 domain epitope present only in the prefusion core of β-coronaviruses: SARS-CoV-2 S2 apex residues 980–1006 in the flexible hinge. Antibody RAY53 binds the native hinge in MERS-CoV and SARS-CoV-2 spikes on the surface of mammalian cells and mediates antibody-dependent cellular phagocytosis and cytotoxicity against SARS-CoV-2 spike in vitro. Hinge epitope mutations that ablate antibody binding compromise pseudovirus infectivity, but changes elsewhere that affect spike opening dynamics, including those found in Omicron BA.1, occlude the epitope and may evade pre-existing serum antibodies targeting the S2 core. This work defines a third class of S2 antibody while providing insights into the potency and limitations of S2 core epitope targeting.